Medical demographics in municipalities in extreme poverty in Brazil - Luizeti, Bárbara Okabaiasse (2022)
Health System in municipalities in extreme poverty in the country. This is an observational, longitudinal and retrospective study based on secondary data provided by the Department of Informatics of the Unified Health System. In total, 16,267 physicians were identified, of which 1,360 worked in the private network and 14,907 in the public network. The regional distribution is as follows: 1,284 in the North; 9,186 in the Northeast; 3,071 in the Southeast; 837 in the South; and 529 in the Midwest. Among Brazilian municipalities in extreme poverty, 12.2% have three physicians; 10.7% of two physicians; and 9.2% of only one. The primary outcomes related to the demographics of medical personnel municipalities in extreme poverty show the disproportion in the distribution of professionals among Brazilian cities. The implementation of health policies that promote the equity of such demographicsin the country is suggested.